Analisis Pengaruh Gaji dan Bonus terhadap Motivasi Kerja Pada Bank Syariah Mandiri KC Medan Gajah Mada - Said Rifky Aulawy; Supaino; Ahmad Kholil (Universitas Muhammadiyah Surabaya, 2024)
This research was conducted to determine the Analysis of the Effect of Salary and Bonus on Work Motivation at PT Bank Syariah Mandiri KC Medan Gajah Mada. The dependent variable in this study is Motivation, while the independent variable consists of Salary and Bonus. The sample in this study was as many as 70 respondents. The research methods used in this study are multiple linear regression, partial test (t), and simultaneous test (F) with the help of SPSS 16 program application. The results of the study with partial test (t) showed that 2 independent variables had a significant effect on the dependent variable because the significance value < 0.05, namely Salary (0.000 < 0.05) and Bonus (0.003 < 0.05) and simultaneously Salary and Bonus have a positive and significant influence on Work Motivation at PT Bank Syariah Mandiri KC Medan Gajah Mada which is seen through statistical test F with a significance value of (0.000 < 0.05).